Establishing a Disease‐in‐a‐Dish Model to Study SARS‐CoV‐2 Infection During Prenatal Development. Issue 4 (26th April 2023) - Song, Ann; Ona, Jack; Osuna, Claudia; Phandthong, Rattapol; Talbot, Prue
Abstract: Mother‐to‐fetus transmission of the SARS‐CoV‐2 virus via the placenta has been reported but cannot readily be studied in pregnant women. This protocol describes an in vitro method to investigate SARS‐CoV‐2 infection of human embryonic stem cells (hESCs), which are similar to epiblast cells in young postimplantation embryos. First, SARS‐CoV‐2 viral pseudoparticles, which contain the spike protein and a fluorescent reporter, are incorporated into a lentivirus backbone that is expanded in HEK 293T cells. Then, an infection assay based on hESCs is used with the viral pseudoparticles. An application of the infection assay in therapeutic drug screening is provided. This protocol allows infection of hESCs by SARS‐CoV‐2 pseudoparticles to be studied in vitro and can be used in conjunction with other assays to understand and potentially prevent infection. hESCs could also be differentiated to study infection in the three germ layers and their fetal cell derivatives. This disease‐in‐a‐dish model could be readily applied to other hESC lines, and to other viral infections, that affect human prenatal development. © 2023 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Preparing HEK 293T cells for lentiviral vector transfection Support Protocol 1 : Visual inspection of transfected HEK 293T cells Basic Protocol 2 : Generating viral pseudoparticles Support Protocol 2 : Determining viral titer with HEK 293T‐ACE2 cells Basic Protocol 3 : Plating hESCs for the infection assay Support Protocol 3 : Evaluating transduction efficiency